2022
DOI: 10.1038/s41467-022-30027-x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping sight of copper in single-atom catalysts for electrochemical carbon dioxide reduction

Abstract: Carbon dioxide can be electrochemically converted into valuable multi-carbon products using Cu-based single-atom catalysts. However, transient cluster formation, which is undetectable using ex-situ techniques, may be responsible for C 2+ products. Here we discuss these observations to highlight the need for operando characterisation when defining active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…17 In addition, a more interesting structural transformation occurred on Cu SACs during CO 2 reduction. Fontecave et al 18,19 reported that single-atom Cu 2+ dispersed in the N-doped carbon material, under a certain range of negative electrode potential, could be transformed into Cu 0 small clusters. In turn, it can be restored to Cu 2+ in the initial atomic dispersion state after releasing the applied potential or switching to a positive potential.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, a more interesting structural transformation occurred on Cu SACs during CO 2 reduction. Fontecave et al 18,19 reported that single-atom Cu 2+ dispersed in the N-doped carbon material, under a certain range of negative electrode potential, could be transformed into Cu 0 small clusters. In turn, it can be restored to Cu 2+ in the initial atomic dispersion state after releasing the applied potential or switching to a positive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these Cu clusters have been proposed to be responsible for the activity of the catalyst towards the CO 2 RR. 6,11 It is important to note that this process is reversible, namely that CuN 4 sites are regenerated upon reoxidation. This seems to be a quite general behaviour of single Cu sites since such a reversible rearrangement of Cu species (the interconversion of single site and clusters), has also been observed with Cu phthalocyanine as well as with O-ligated single Cu atoms anchored in oxygenated carbon, 12,13 as clearly established by operando XAS.…”
Section: Introductionmentioning
confidence: 99%
“…However, previously reported catalysts suffered from the easy desorption of *CO intermediate and the aggregation into copper clusters in the electrocatalysis process. [10] Compared with inorganic catalysts, crystalline metal complexes have the advantages of clear catalytic sites and structural designability. [11] As crystalline porous materials, a number of two-dimensional (2D) conductive covalent-organic frame-works (COFs), [12] compared to metal-organic frameworks, are constructed through covalent bonds, endowing them with impressive stability for device application.…”
mentioning
confidence: 99%